A search strategy for occupational health intervention studies. Issue 10 (16th September 2005) - Verbeek, J; Salmi, J; Pasternack, I; Jauhiainen, M; Laamanen, I; Schaafsma, F; Hulshof, C; van Dijk, F
Abstract : Background: As a result of low numbers and diversity in study type, occupational health intervention studies are not easy to locate in electronic literature databases. Aim: To develop a search strategy that facilitates finding occupational health intervention studies in Medline, both for researchers and practitioners. Methods: A gold standard of articles was created by going through two whole volumes of 19 biomedical journals, both occupational health specialty and non-occupational health journals. Criteria for occupational health intervention studies were: evaluating an intervention with an occupational health outcome and a study design with a control group. Each journal was searched independently by two of the authors. Search terms were developed by asking specialists and counting word frequencies in gold standard articles. Results: Out of 11 022 articles published we found 149 occupational health intervention studies. The most sensitive single terms were work*[tw] (sensitivity 71%, specificity 88%) and effect*[tw] (sensitivity 75%, specificity 63%). The most sensitive string was (effect*[tw] OR control*[tw] OR evaluation*[tw] OR program*[tw]) AND (work*[tw] OR occupation*[tw] OR prevention*[tw] OR protect*[tw]) (sensitivity 89%, specificity 78%). The most specific single terms were "occupational health"[tw] (sensitivity 22%, specificity 98%) and effectiveness[tw] (sensitivity 22%, specificity 98%). The most specific string was (program[tw] OR "prevention and control"[sh]) AND (occupational[tw] OR worker*[tw]) (sensitivity 47%, specificity 98%). Conclusion: No single search terms are available that can locate occupational health intervention studies sufficiently. The authors' search strings have acceptable sensitivity and specificity to be used by researchers and practitioners respectively. Redefinition and elaboration of keywords in Medline could greatly facilitate the location of occupational health intervention studies.